On the scattered field generated by a ball inhomogeneity of constant index - Capdeboscq, Y (Society for Industrial and Applied Mathematics, 2012)
We consider the solution of a scalar Helmholtz equation where the potential (or index) takes two positive values, one inside a disk of radius $ε$ and another one outside. We derive sharp estimates of the size of the scattered field caused by this disk inhomogeneity, for any frequencies and any contrast. We also provide a broadband estimate, that is, a uniform bound for the scattered field for any contrast, and any frequencies outside of a set which tend to zero with $ε$.